Practitioner observations of oral nicotine use in elite sport: You snus you lose - Kasper, A. M.; Close, G. L. (European Journal of Sport Science, 2020)
The elite sport environment is one where athletes strive to find a competitive edge, through improved recovery modalities, cognitive performance or physical capacity. Due to this, non-scientifically evidenced and/or pseudo-scientific alternative remedies are ever popular. Snus (an oral tobacco based product containing the highly addictive compound nicotine) is one alternative `physical and psychological performance enhancer`, purported to act as a `mental and physical booster`, `relaxative` and even as an `appetite suppressor`. Despite snus having serious adverse health effects, along with no proven benefit to physical or mental performance, observations by the authors working in professional sport, along with several reports in the mainstream media, would suggest that the use of snus in elite sport appears to be increasing. Perhaps most worrying, the use of snus has been reported to be prevalent within younger athletes. It is crucial that athletes are fully educated with regards to the health implications of snus and other oral tobacco-based products, whilst practitioners should be aware of its growing prevalence in sport with strategies in place to discourage its use.